A case of spontaneous mesenteric hematoma successfully diagnosed and treated with aggressive imaging. (2019) - Nakamura, Shunsuke; Yamada, Taihei; Nojima, Tsuyoshi; Naito, Hiromichi; Koga, Hitoshi; Yamashita, Hisashi; Gochi, Akira; Nakao, Atsunori
Highlights: Spontaneous mesenteric hematoma is an uncommon syndrome, and often misdiagnosed as other non-hemorrhagic acute abdomen. Close monitoring for any signs of further deterioration, as well as aggressive imaging diagnosis, enabled us to make early diagnosis and treatment. Sharing our experience may help physicians initiate treatment of mesenteric hematomas early to prevent life-threatening adverse events. Abstract: Introduction: Spontaneous mesenteric hematoma is an uncommon syndrome triggered by bleeding localized in the mesenteric vascular tree of a bowel segment for no apparent underlying reason. We herein report a surgical patient with an extremely rapidly growing spontaneous mesenteric hematoma that we successfully diagnosed using careful radiologic examination. Presentation of case: A 56-year-old old male presenting sudden onset lower abdominal pain was referred to our emergency department. At the time of admission, his physical examination revealed stable vital signs without radiological abnormality. On the following day, the patient suddenly presented hypotension, tachycardia, and increased abdominal pain. Contrast-enhanced computed tomography examination showed a mass with both high- and low-density areas with a 130 mm maximum diameter bordering the transverse colon. Since interventional radiologists were not available, we decided to perform emergency exploratory laparotomy. On laparotomy, a 13 × 8 cm hematoma was found in the mesentery of the transverse colon. As bleeding was noted from the branches of the middle colic artery and gastrocolic artery, these responsible vessels were ligated. The patient was finally given the diagnosis of spontaneous mesenteric hematoma. Discussion and conclusion: The present case, initially diagnosed as enterocolitis, suddenly manifested hypovolemic shock. Close monitoring for any signs of further deterioration, as well as aggressive imaging diagnosis, enabled us to avoid delays in treatment. Early diagnosis and treatment of mesenteric hematomas are essential to prevent them from rupturing and triggering life-threatening adverse events.